Aplikasi Articulate Storyline Tentang Pencegahan Virus Covid-19 Untuk Siswa Sekolah Dasar - Andre Kurniadi; Dholina Inang Pambudi (Pusat Pengembangan Pendidikan dan Bakat Indonesia, 2022)
The Covid-19 virus pandemic has prompted the government of Indonesia to implement policies regarding health protocols for all citizens including elementary school students. However, elementary school-age children are still unable to understand the importance of implementing these health protocols properly. This study aims to: 1) determine the development of interactive Articulate Storyline media on the prevention of Covid-19 virus transmission for elementary school students; 2) determine the quality of the development of interactive Articulate Storyline media on the prevention of Covid-19 virus transmission for elementary school students. This study was conducted in the form of Research and Development (R&D) research using the ADDIE development model. The development model consists of 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research data were drawn from expert judgment. A combination of qualitative and quantitative approaches were used to analyze the data. The results of this study based on the assessment from the experts were as follows. The assessment results of media experts and material experts revealed that the developed product was categorized as